PPAR-γ Modulators as Current and Potential Cancer Treatments - Chi, Tiange; Wang, Mina; Wang, Xu; Yang, Ke; Xie, Feiyu; Liao, Zehuan; Wei, Peng (Frontiers in Oncology, 2021)
Worldwide, cancer has become one of the leading causes of mortality. Peroxisome Proliferator-Activated Receptors (PPARs) is a family of critical sensors of lipids as well as regulators of diverse metabolic pathways. They are also equipped with the capability to promote eNOS activation, regulate immunity and inflammation response. Aside from the established properties, emerging discoveries are also made in PPAR’s functions in the cancer field. All considerations are given, there exists great potential in PPAR modulators which may hold in the management of cancers. In particular, PPAR-γ, the most expressed subtype in adipose tissues with two isoforms of different tissue distribution, has been proven to be able to inhibit cell proliferation, induce cell cycle termination and apoptosis of multiple cancer cells, promote intercellular adhesion, and cripple the inflamed state of tumor microenvironment, both on transcriptional and protein level. However, despite the multi-functionalities, the safety of PPAR-γ modulators is still of clinical concern in terms of dosage, drug interactions, cancer types and stages, etc. This review aims to consolidate the functions of PPAR-γ, the current and potential applications of PPAR-γ modulators, and the challenges in applying PPAR-γ modulators to cancer treatment, in both laboratory and clinical settings. We sincerely hope to provide a comprehensive perspective on the prospect of PPAR-γ applicability in the field of cancer treatment.